1995
DOI: 10.1111/j.1469-8749.1995.tb11967.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Physicians‘ Decisions to Refer Children With Cerebral Pai Sy for Physical Therapy

Abstract: SUMMARY Videotapes of ten children with ‘suspected’ cerebral palsy were used as stimuli to elicit physicians' decisions regarding referral for physical therapy. Respondents were 99 developmental or general pediatricians, orthopaedists, neurologists or physiatrists who were membes of the American Academy of Pediatrics or the American Academy of Cerebral Palsy. They rated their belief in the value of therapy; described their exprience, training and practices relating to management of cerebral palsy; and responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, we found no differences in waiting times between children who were identified as having moderate or severe functional disabilities and those who had mild disabilities. Our initial hypothesis was that children with mild disabilities would wait longer for rehabilitation services, since there may be a propensity towards providing services sooner to children with severe disabilities (Campbell et al 1995). Our results may reflect a phenomenon whereby those who are diagnosed at a younger age may have a more severe degree of disability.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…However, we found no differences in waiting times between children who were identified as having moderate or severe functional disabilities and those who had mild disabilities. Our initial hypothesis was that children with mild disabilities would wait longer for rehabilitation services, since there may be a propensity towards providing services sooner to children with severe disabilities (Campbell et al 1995). Our results may reflect a phenomenon whereby those who are diagnosed at a younger age may have a more severe degree of disability.…”
Section: Discussionmentioning
confidence: 49%
“…These results suggest that coordinators at the rehabilitation centres may prioritize younger children to ensure the greatest benefits from early rehabilitation intervention (Office des personnes handicapées du Québec 1992; American Academy of Pediatrics 1996Pediatrics , 2001Shevell et al 2000Shevell et al , 2001Halfon et al 2004;Majnemer 1998). Perceived diagnostic certainty by physicians has been shown to influence referral of children to rehabilitation (Campbell et al 1995;Majnemer et al 2002;Shevell et al 2001). One study found that the higher the certainty that a child had cerebral palsy, the higher the odds of referral to rehabilitation (Campbell et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations